2009
DOI: 10.1002/btpr.312
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of flow conditions in 2 L and 20 L wave bioreactors® using computational fluid dynamics

Abstract: Characterization of flow conditions is of great importance to control cell growth and cell damage in animal cell culture because cell viability is influenced by the flow properties in bioreactors. Alternative reactor types like Wave Bioreactors have been proposed in recent years, leading to markedly different results in cell growth and product formation. An advantage of Wave Bioreactors is the disposability of the Polyethylenterephthalet-bags after one single use (fast setup of new production facilities). Anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 39 publications
(41 reference statements)
2
19
0
Order By: Relevance
“…As the platform rotates upward again (Figure H) the fluid accelerates in the horizontal direction to achieve the velocity field shown in Figure A. Similarly, to what was observed in this work, Oncul et al (2009) measured velocities using a hot‐film velocity probe at various positions within a 2 L bag, at a rocking speed N = 15 rpm and 7° rocking angle, and reported higher velocities in the middle of the bag at x/L = 0.5 compared to the bag edges.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…As the platform rotates upward again (Figure H) the fluid accelerates in the horizontal direction to achieve the velocity field shown in Figure A. Similarly, to what was observed in this work, Oncul et al (2009) measured velocities using a hot‐film velocity probe at various positions within a 2 L bag, at a rocking speed N = 15 rpm and 7° rocking angle, and reported higher velocities in the middle of the bag at x/L = 0.5 compared to the bag edges.…”
Section: Resultssupporting
confidence: 81%
“…Fluid velocities measured by Oncul et al in a 2 L rocked bag at N = 15 rpm showed a similar trend, with maximum average velocities of 0.1–0.2 ms −1 reported at various locations in the bag at an inclination of α = 0°, and minimum average velocity values around or less than 0.02 ms −2 obtained at α = 8°. The volumetric flow rate estimation described by Eq.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…14.3, where Δx represents the maximum fluid element displacement in the vessel during one rocking cycle, which is hard to determine experimentally. It has been stated that turbulent conditions appear in oscillating flows when β exceeds 700 for Wo greater than 8.5 (Oncül et al 2009). …”
Section: Wave-mixed Bag Bioreactorsmentioning
confidence: 98%
“…In contrast, the non-dimensional Womersley number (Wo), a classical non-dimensional number, and a parameter β were used to quantify the unsteady nature of the flows (Oncül et al 2009). Wo is expressed by Eq.…”
Section: Wave-mixed Bag Bioreactorsmentioning
confidence: 99%